Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Optical properties of semiconductor photonic-crystal structures: spatially-inhomogeneous excitonic resonances and optical gain - Meier, Torsten; Reichelt, Matthias; Pasenow, B.; Stroucken, T.; Koch, S.W. (2005 annual conference of the German Physical Society (DPG) during the World year of physics)

Nonlinear optical response of the Si ( 111 ) − ( 2 × 1 ) surface exciton: Influence of biexciton many-body correlations - Oszwałdowski, R.; Reichelt, Matthias; Meier, Torsten; Koch, S. W.; Rohlfing, Michael (Physical Review B)

Nonlinear optical properties of semiconductor quantum wells inside microcavities - Meier, Torsten; Sieh, C.; Koch, S.W.; Lee, Y.-S; Norris, T.B.; Jahnke, F.; Khitrova, G.; Gibbs , H.M. (Optical Microcavities)
Experimental results on the nonlinear optical properties of semiconductors are compared with microscopic calculations which include Coulomb many-body correlations at different levels. One aim of this chapter is to show that microscopic theories, which have been developed for bare semiconductor heterostructures, are also able to describe semiconductor microcavities very well. Therefore, there is no need to phenomenologically introduce polariton-polariton interactions and parametric scattering of cavity polaritons to describe microcavity experiments, but instead a fully microscopic theory based on a Fermionic electron-hole Hamiltonian can be used. The treatment of many-body correlations using the second-order Born approximation and the dynamics-controlled truncation scheme are introduced and analyzed for bare heterostructures. These approaches are able to successfully explain a number of important experimental results which originate from the dynamics of many-body correlations. Then measurements of the nonlinear optical properties of a quantum-well microcavity are described. In these experiments the spectrally- and temporally-resolved nonlinear optical response is studied in detail using a pump-probe geometry. In particular, the polarization and intensity dependencies of the spectral probe reflection changes and their temporal evolution are analyzed. The prominent features of these experiments are well accounted for by the microscopic many-body theory.

Fano resonances in metallic photonic crystals - Meier, Torsten; Giessen, H.; Linden, S.; Christ, A.; Kuhl, J.; Nau, D.; Thomas, P.; Koch, S.W. (Fano resonances in metallic photonic crystals)
We demonstrate that interference of optical excitations of regularly arranged metallic nanodots on a waveguide shows spectral signatures of Fano resonances. The reason is coupling of localized particle plasmons and waveguide modes with different electronic continua.

Onset of Dynamical Localization in a Semiconductor Superlattice - Meier, Torsten; Koch, M.; Ciulin, V.; Carter, S.G.; Sherwin, M.S.; Koch, S.W.; Zide, J.; Driscoll, D.; Gossard, A.C. (International Quantum Electronics Conference)
An excitonic blue-shift is observed when a GaAs/AlGaAs superlattice is irradiated with a strong THz field. This observation is compared with a microscopic calculation, and is consistent with the onset of dynamical localization.

Five-Wave-Mixing Spectroscopy of Ultrafast Electron Dynamics at a Si(001) Surface - Voelkmann, C.; Reichelt, Matthias; Meier, Torsten; Koch, S. W.; Höfer, U. (Physical Review Letters)
The optically induced electron dynamics at a Si(001) surface is studied using a five-wave-mixing setup which measures the diffracted second-harmonic intensity induced by three ultrashort (13 fs) laser pulses. Depending on the time ordering of the pulses, this technique is capable of monitoring the temporal evolution of photoexcited one- or two-photon coherences, or populations. For a particular pulse sequence, the experiments show a delayed rise and a decay of the diffracted signal intensity on time scales of 50 and 250 fs, respectively. This response can be described by optical Bloch equations by including rapid scattering of the photoexcited carriers in the D(down)band of Si(001).

Nonequilibrium gain in optically pumped GaInNAs laser structures - Thränhardt, A.; Becker, S.; Schlichenmaier, C.; Kuznetsova, I.; Meier, Torsten; Koch, S. W.; Hader, J.; Moloney, J. V.; Chow, W. W. (Applied Physics Letters)
A theory is presented which couples a dynamical laser model to a fully microscopic calculation of scattering effects. Calculations for two optically pumped GaInNAs laser structures show how this approach can be used to analyze nonequilibrium and dynamical laser properties over a wide range of system parameters.

Semiconductor Optics in Photonic Crystal Structures - Meier, Torsten; Koch, Stephan W. (Photonic Crystals: Advances in Design, Fabrication, and Characterization)

Dynamics of short-time-scale energy relaxation of optical excitations due to electron-electron scattering in the presence of arbitrary disorder - Meier, Torsten; Varga, I.; Thomas, P.; Koch, S.W. (Physical Review B)
A nonequilibrium occupation distribution relaxes towards the Fermi-Dirac distribution due to electron-electron scattering even in finite Fermi systems. The dynamic evolution of this thermalization process assumed to result from an optical excitation is investigated numerically by solving a Boltzmann equation for the carrier populations using a one-dimensional disordered system. We focus on the short-time-scale behavior. The logarithmically long time scale associated with the glassy behavior of interacting electrons in disordered systems is not treated in our investigation. For weak disorder and short range interaction we recover the expected result that the relaxation rate is enhanced by disorder. For sufficiently strong disorder, however, we find an opposite trend due to the reduction of scattering probabilities originating from the strong localization of the single-particle states. Long-range interaction in this regime produces a similar effect. The relaxation rate is found to scale with the interaction strength, however, the interplay between the implicit and the explicit character of the interaction produces an anomalous exponent.

Theory for the nonlinear optical response of semiconductor surfaces: Application to the optical Stark effect and spectral oscillations of the Si(111)-(2x1) surface exciton - Meier, Torsten; Reichelt, Matthias; Koch, S.W.; Rohlfing, M. (Physical Review B)
A microscopic approach is presented to compute nonlinear optical properties of semiconductor surfaces. The method uses quasiparticle wave functions and dispersions obtained from ab initio band-structure theory as an input for Bloch equations which describe the optical properties. Excitonic effects in the linear absorption spectra of the Si(111)- (2×1) surface are obtained by integrating equations of motion. To demonstrate the applicability of the approach for analyzing nonlinear optical properties, ultrafast light-intensity-dependent absorption changes of the surface exciton are predicted. The numerical results discuss the optical Stark effect and spectral oscillations of the surface exciton which can both be observed in pump-probe experiments.

Signatures of biexcitons and triexcitons in coherent non-degenerate semiconductor optics - Meier, Torsten; Sieh, C.; Finger, E.; Stolz, W.; Rühle, W.W.; Koch, S.W.; Thomas, P. (physica status solidi (b))
Signatures of exciton and two-exciton states in semiconductor systems are investigated experimentally and theoretically. A set of quantum well samples with different well widths is studied using coherent excitation spectroscopy. The experimental results are analyzed using a microscopic model demonstrating the importance of biexciton correlations and disorder effects. Additional numerical investigations of absorption changes in small nanorings are employed to analyze optical transitions from two-exciton to three-exciton resonances.

Dynamics of short-time-scale energy relaxation of optical excitations due to electron-electron scattering in the presence of arbitrary disorder - Varga, Imre; Thomas, Peter; Meier, Torsten; Koch, Stephan W. (Physical Review B)
A nonequilibrium occupation distribution relaxes towards the Fermi-Dirac distribution due to electron-electron scattering even in finite Fermi systems. The dynamic evolution of this thermalization process assumed to result from an optical excitation is investigated numerically by solving a Boltzmann equation for the carrier populations using a one-dimensional disordered system. We focus on the short-time-scale behavior. The logarithmically long time scale associated with the glassy behavior of interacting electrons in disordered systems is not treated in our investigation. For weak disorder and short range interaction we recover the expected result that the relaxation rate is enhanced by disorder. For sufficiently strong disorder, however, we find an opposite trend due to the reduction of scattering probabilities originating from the strong localization of the single-particle states. Long-range interaction in this regime produces a similar effect. The relaxation rate is found to scale with the interaction strength, however, the interplay between the implicit and the explicit character of the interaction produces an anomalous exponent.

Electronic transport in a one-dimensional random array of scatterers - Meier, Torsten; Filinov, V.S.; Thomas, P.; Varga, I.; Bonitz, M.; Fortov, V.E; Koch, S.W. (Journal of Physics A: Mathematical and General)
The quantum dynamics of an ensemble of interacting electrons in an array of random scatterers is treated using a new numerical approach for the calculation of average values of quantum operators and time correlation functions in the Wigner representation. This approach combines both molecular dynamics and Monte Carlo methods and computes numerical traces and spectra of the relevant dynamical quantities such as momentum–momentum correlation functions and spatial dispersions. Considering, as an application, a system with fixed scatterers, the results clearly demonstrate that the many-particle interaction between the electrons can lead to an enhancement of the conductivity at intermediate densities.

Wigner approach to quantum dynamics simulations of the interacting carriers in disordered systems - Meier, Torsten; Filinov, V.; Thomas, P.; Bonitz, M.; Fortov, V.; Varga, I. (physica status solidi (b))
The new method for solving Wigner–Liouville's type equations and studying dynamics of quantum particles has been developed within the Wigner formulation of quantum statistical mechanics. This approach combines both molecular dynamics and Monte Carlo methods and computes traces and spectra of the relevant dynamical quantities. Considering, as an application, the quantum dynamics of an ensemble of interacting electrons in an array of random scatterers clearly demonstrates that the many-particle interaction between the electrons can lead to an enhancement of the electrical conductivity.

Semiconductor photonic-crystal structures: Optical spectra and carrier dynamics - Meier, Torsten

Microscopic theory for the nonlinear optical response of semiconductor surfaces: Application to the optical Stark effect of the Si(111)-(2x1) surface exciton - Meier, Torsten; Reichelt, Matthias; Koch, S.W.; Rohlfing, M. (physica status solidi (b))
A novel microscopic approach for computing nonlinear optical properties of semiconductor surfaces is outlined. The linear and nonlinear response of the Si(111)-(2×1) surface is studied using a combination of ab-initio band-structure theory and equation of motion technique. The usefulness of the method is shown by reproducing known excitonic effects in the linear differential reflectivity spectrum. To additionally demonstrate the applicability of the approach for the nonlinear regime, the nonlinear optical response in Stark effect configuration is examined.

Semiconductor excitons in photonic crystals - Meier, Torsten; Eichmann, R.; Pasenow, B.; Thomas, P.; Koch, S.W. (physica status solidi (b))
Optical properties of a semiconductor quantum well in the vicinity of a two-dimensional photonic crystal are investigated. Due to the periodic spatial modulation of the dielectric environment the effective Coulomb interaction potential exhibits the periodicity of the photonic crystal. As a consequence, the excitonic binding energy varies periodically by up to 50% depending on the spatial position of the exciton relative to the structured dielectric. The self image charge effects result in a position dependent shift of the single-particle bandgap such that the spectral position of the absorption spectrum also develops the periodicity of the photonic surrounding.

Semiconductor absorption in photonic crystals - Eichmann, R.; Pasenow, B.; Meier, Torsten; Stroucken, T.; Thomas, P.; Koch, S.W. (Applied Physics Letters)
Absorption spectra of semiconductor structures in photonic crystal environments are investigated numerically. It is shown that the periodic dielectric structuring changes the local optical and Coulomb interaction properties of semiconductor electron–hole excitations. The structurally induced modifications offer the possibility to design important aspects of the optoelectronic semiconductor properties.